Current situation of the pandemic in Brazil: technological innovation, advances in Science and challenges (Research, Society and Development, 2021)
The 2019 Coronavirus disease pandemic showed that the world was not sufficiently prepared to face emerging epidemics, exposing great global sanitary and socioeconomic vulnerability, especially in underdeveloped countries like Brazil, being the second country with the highest number of contagion rates and deaths, surpassing the 600 thousand deaths mark. The objective of this review is to identify drugs and vaccines in development and discuss the main challenges of the pandemic in Brazil. With the rapid advance of the pandemic, a technological race for the development of vaccines against the coronavirus began. There are currently more than 300 vaccines under development against COVID-19, among them 18 are being developed by Brazilian institutes. In addition, the emergency use of 4 candidate vaccines was approved, namely: Covisheield, Comirnaty, Coronavac and Janssen. The fight against the pandemic in Brazil comes up against obstacles such as lack of basic sanitation, limited access to health services and quality education, in addition to mistaken actions or omissions by the public authorities and the widespread dissemination of misinformation about the disease, which contributed to the an increase in the number of cases, and a weakening of the health system. Currently, the advance in vaccination of 58.25% of the adult population with a complete vaccination schedule has resulted in a consistent drop in cases and deaths, thanks to a solid state structure of a vaccination program with high capillarity and high popular acceptance of the vaccine.